Diseño e implementación de un manual de operación, mantenimiento y seguridad del taladro fresador modelo nº 40n2f del centro de producción y servicios de la Universidad Técnica de Cotopaxi, ubicada en la ciudad de Latacunga, año lectivo 2011- 2012 - Sinchiguano Panchi, Héctor Ramiro (2015)
This research is the guide to define procedures, conservation and control to the proper use of drill milling that the Production and Service Center of the Technical University of Cotopaxi has in order to help the scientific and technologic development to the social problems elaboration of projects integrating theoretic with practicing. Drill milling was imported so its manuals will be not understand easily by the operator in instead of generating a good development, it decreases the quality of the production, consequently the aim of this research is defining and setting up an Operational Manual ,maintenance and security of drill milling MODEL N˚ 40N2F, applying all types of maintenances to raise its life, determining the additional accessories for its optimum performance and the appreciation of the use in each of the finished products. It is contributing to consolidate the knowledge around this working machine to get processes of high level and it becomes in sources of income for the institution....